2020
DOI: 10.3390/antiox9111118
|View full text |Cite
|
Sign up to set email alerts
|

MARGRA Lamb Eating Quality and Human Health-Promoting Omega-3 Long-Chain Polyunsaturated Fatty Acid Profiles of Tattykeel Australian White Sheep: Linebreeding and Gender Effects

Abstract: Health-conscious consumers increasingly demand healthier, tastier, and more nutritious meat, hence the continuous need to meet market specifications and demand for high-quality lamb. We evaluated the longissimus dorsi muscle of 147 Tattykeel Australian White (TAW) sheep fed on antioxidant-rich ryegrass pastures exclusive to MAGRA lamb brand for meat eating quality parameters of intramuscular fat (IMF) content, fat melting point (FMP) and omega-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA). The aim was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 86 publications
(53 reference statements)
1
12
0
Order By: Relevance
“…The level of incorporation and abundance of both monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids in the muscle is consistent with previously reported intramuscular fatty acid compositions [56,57]. A review of pre-clinical and human trials with conjugated linoleic acid CLA (C18:2n-6) revealed positive effects on cancer, obesity, and atherosclerosis [58,59], and the muscle in the present study had significantly incorporated levels of CLA and ALA (C18:3n-3).…”
Section: Discussionsupporting
confidence: 91%
“…The level of incorporation and abundance of both monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids in the muscle is consistent with previously reported intramuscular fatty acid compositions [56,57]. A review of pre-clinical and human trials with conjugated linoleic acid CLA (C18:2n-6) revealed positive effects on cancer, obesity, and atherosclerosis [58,59], and the muscle in the present study had significantly incorporated levels of CLA and ALA (C18:3n-3).…”
Section: Discussionsupporting
confidence: 91%
“…The Poll Dorset and Texel were used as positive control and the Rambouillet as the negative control in assessing extracted genomic DNA, polymerase chain reaction products, and next-generation sequencing procedures in the laboratory. Details of the muscle biopsy procedure and laboratory analyses of IMF, FMP, and fatty acid composition had already been published [2] and are only briefly summarized below.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The biopsy procedure for sampling the Longissimus dorsi muscle from the 12th-13th ribs was first described in cattle [20] and modified in sheep [2]. Pewan et al [2] published the details of the biopsy procedure in sheep, and these will not be repeated here.…”
Section: Muscle Biopsy Sampling Proceduresmentioning
confidence: 99%
See 2 more Smart Citations